Carotid Intima-Media Thickness and Midlife Cognitive Function: Impact of Race and Social Disparities in the Bogalusa Heart Study. (3rd May 2022) - De Anda-Duran, Ileana; Alonso, Camilo Fernandez; Libon, David J.; Carmichael, Owen T.; Kolachalama, Vijaya B.; Suglia, Shakira F.; Au, Rhoda; Bazzano, Lydia A.
Abstract : Background and Objectives: Carotid intima-media thickness (c-IMT) is a measurement of atherosclerosis, a progressive disease that develops as early as childhood and has been linked with cognitive impairment and dementia in the elderly. However, the relationship between c-IMT and midlife cognitive function and the race and social disparities in this relationship remain unclear. We examined the association between c-IMT and cognitive function in midlife among Black and White participants from a semirural community-based cohort in Bogalusa, Louisiana. Methods: In this cross-sectional analysis of participants from the Bogalusa Heart Study, linear regression models were used to determine the association between c-IMT dichotomized above the 50th percentile (>0.87 mm), an a demographically standardized global cognitive score (GCS), and individual cognitive domain–based z scores. Stratified analyses were performed to evaluate the impact of race and the individual's education status. Results: A total of 1, 217 participants (age 48 ± 5.28 years) were included; 66% (804) self-identified as White, and 34% (413) self-identified as Black. Of those, 58% (708) were women, and 42% (509) were men. Having a c-IMT ≥50th percentile was inversely associated with GCS ( B ± SE −0.39 ± 0.18, p = 0.03), independently of cardiovascular risk factors (CVRFs) and achieved education. The effect remained significant in Black and White participants after adjustment for CVRFs (Black participants: B ± SE −1.25 ± 0.45, p = 0.005; White participants: B ± SE −0.92 ± 0.35, p = 0.008) but not for education. The interaction between c-IMT ≥50th percentile and education was significant ( p = 0.03), and stratified analysis showed an association with GCS among those with lower achieved education ( B ± SE −0.81 ± 0.33, p = 0.013) independently of major CVRFs. Discussion: Subclinical atherosclerosis, measured as c-IMT, was associated with worse midlife cognitive function, independently of major CVRFs. The association was buffered by education and may be stronger among Black than White participants, likely due to corresponding structural and social determinants. These findings underscore the importance of establishing preventive measures in midlife and suggest subclinical atherosclerosis as a potential target to prevent cognitive decline.